2015
DOI: 10.1021/ef5028839
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Inherent Oxygen in Solid Fuels during Pyrolysis

Abstract: Inherent oxygen in solid fuels is various in content and occurrence mode related to other elements. Three samples with different inherent oxygen contents were pyrolyzed in an externally heated fixed-bed reactor to characterize their oxygen transformation among solid, water, and gas products in addition to understanding their pyrolysis performances. It was found that the oxygen retained in the solid char decreased with increasing temperature. About 30–50% of the inherent oxygen has transferred into water after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The amount of N–H/O–H and C–O–C functional groups decreased with increasing temperature. O–H functional groups mainly exist in phenol at 700 °C . Moreover, the peaks of C–H and amide functional groups disappeared at 600 °C.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The amount of N–H/O–H and C–O–C functional groups decreased with increasing temperature. O–H functional groups mainly exist in phenol at 700 °C . Moreover, the peaks of C–H and amide functional groups disappeared at 600 °C.…”
Section: Resultsmentioning
confidence: 97%
“…At 400 °C, the C in C O/[C–( C O)] decreased to 0.31 wt %, which might be caused by the decarboxylation of amino acids and the decarbonylation of organic functional groups. Dong et al showed that the decomposition of carboxyl groups in biomass mainly occurred at temperatures less than 400 °C. Table S2 showed that the content of H in the biochar decreased from 3.85 wt % at 400 °C to 1.29 wt % at 700 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…X‐ray photoelectron spectroscopy (XPS) analysis (Table ) reveals that sample Fd‐AC contains less surface O content than sample AC, which results from the more efficient activation in Fd‐AC by vacuum freeze‐drying. Because high‐temperature annealing is an effective method to eliminate oxygen atoms, sample Fd‐AC‐a has the least surface O content. The low oxygen content is of great benefit to enhance the EDLC life span of Fd‐AC‐a at voltages over 2.5 V.…”
Section: Resultsmentioning
confidence: 99%
“…52,66 On the contrary, the relative contents of C−O groups after LZ pyrolysis was found out to increase from 11.9% to 21.24%, mainly due to their formation through both elimination of the hydroxyl groups 65 as well as the breakage of CO groups. 67 Meanwhile, after LZ pyrolysis, more COOH groups were formed through the further conversion of the formed C−O groups, 68,69 though COOH groups were reported as thermally unstable 70 and easily decomposed through decarboxylation reaction to form H 2 O and CO 2 , as discussed in Section 3.4 above.…”
Section: Energy and Fuelsmentioning
confidence: 99%